Biostimulants in protected cultivation: Unlocking growth potential in horticultural crops - Deepika, N; Kumutha, K; Sabarinathan, K G; Vijayapriya, P; Ananthan, M; Amutha, R (Plant Science Today, 2025)
Plant biostimulants are materials or microorganisms with high nutrient contents that are applied to plants to promote seed germination, stimulate growth and maturation and increase nutrient use efficiency. Biostimulants such as humic acid, seaweed extracts, protein hydrolysates, microbial formulations and inorganic biostimulants are used to increase plant growth, nutrient absorption and stress tolerance. Humic biostimulants enhance the nourishment of roots, while protein-derived biostimulants affect nitrogen uptake and the assimilation process. Microbial stimulants can act through various direct and indirect mechanisms, whereas seaweed biostimulants increase microbial activity, improve nutrient uptake and promote plant growth and soil health. By improving nutrient use efficiency, enhancing stress tolerance and promoting overall crop quality, biostimulants offer sustainable alternatives to conventional inputs. Biostimulants are predominantly used for high-value horticultural crops to improve flowering, yield, quality and shelf-life. Many vegetable growers face challenges due to adverse weather conditions, leading to the adoption of protected cultivation as a high-intensity method to enable year-round production. Biostimulants have been proposed as an effective strategy to promote ecofriendly agriculture, alleviate biotic and abiotic stresses under protected cultivation and reduce the cost of chemical inputs. This review describes the types and functions of biostimulants and their effects on major horticultural crops, with an emphasis on their applications in structured cultivation systems.